Deployable electronics with enhanced fatigue resistance for crumpling and tension - Hong, Insic; Roh, Yeonwook; Cho, Junggwang; Lee, Seunggon; Kang, Minji; Choi, Damin; Gong, Dohyeon; An, Hyeongi; Lim, Daseul; Shin, Dongwook; Park, Jieun; Kim, Changhwan; et al. (Science Advances, 2025)
Highly packable and deployable electronics offer a variety of advantages in electronics and robotics by facilitating spatial efficiency. These electronics must endure extreme folding during packaging and tension to maintain a rigid structure in the deployment state. Here, we present foldable and robustly deployable electronics inspired by Plantago, characterized by their tolerance to folding and tension due to integration of tough veins within thin leaf. The primary design approach for these electronics involves a high resistance to folding and tension, achieved through a thin multilayered electronic composite, which manages the neutral axis and incorporates tough Kevlar. The fabricated electronics can be folded up to 750,000 times without malfunctions and endure pulling an object 6667 times heavier than itself without stretching. Such robust electronics can be used as a deployable robot with sensor arrays, demonstrating practical applicability, as it maintains their mechanical and electrical properties during inflation from the packaged state.
Keywords: Design approaches; Electronic composites; Fatigue-resistance; Foldings; High resistance; Multi-layered; Neutral axis; Plantago; Primary design; Sensors array